In vitro antibiotic susceptibility testing of Brucella isolates from Egypt between 1999 and 2007 and evidence of probable rifampin resistance - Abdel-Maksoud Mohamed; House Brent; Wasfy Momtaz; Abdel-Rahman Bassem; Pimentel Guillermo; Roushdy Gehan; Dueger Erica (BMC, 2012)
Abstract Background Brucellosis poses a significant public health problem in Mediterranean countries, including Egypt. Treatment of this disease is often empirical due to limited information on the antibiotic susceptibility profiles of Brucella spp. in this region of the world. The aim of this study was to determine the antibiotic susceptibility profiles of Brucella blood isolates in Egypt, a country endemic for brucellosis. Methods Brucella spp. isolates were identified from the blood cultures of acute febrile illness (AFI) patients presenting to a network of infectious disease hospitals from 1999-2007. Minimum inhibitory concentrations were determined for tetracycline, gentamicin, doxycycline, trimethoprim-sulfamethoxazole, streptomycin, ceftriaxone, ciprofloxacin and rifampin using the E-test. Interpretations were made according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Results A total of 355 Brucella spp. isolates were analyzed. All were susceptible to tetracycline, doxycycline, trimethoprim-sulfamethoxazole, streptomycin and ciprofloxacin; probable resistance to rifampin and ceftriaxone was observed among 277 (64%) and 7 (2%) of the isolates, respectively. Percentages of isolates showing probable resistance to rifampin were significantly lower before 2001 than in the following years (7% vs. >81%, p < 0.01). Conclusions Despite the high burden of brucellosis in Egypt and frequent empirical treatment, isolates have remained susceptible to the majority of tested antibiotics. However, this is the first report of high rates of probable resistance to rifampin among Brucella isolates from Egypt. Patients should be closely monitored while following standard treatment regimens. Continued surveillance, drug susceptibility studies and updated CLSI interpretive criteria are needed to monitor and update antibiotic prescribing policies for brucellosis.